Pengaruh Kepemilikan Publik, Ukuran Perusahaan, Environmental Performance, dan Profitabilitas Terhadap Environmental Disclosure pada Perusahaan Energi yang Terdaftar di Bursa Efek Indonesia Tahun 2019-2022 - Hapsari, Martania Dwi; Nugraheni, Agustina Prativi; Arifah, Siti (Pusat P2M Politeknik Negeri Batam, 2024)
This research aims to test empirically about the influence of public ownership, company size, environmental performance, and profitability towards environmental disclosure in the energy companies which are registered on the Indonesia Stock Exchange in 2019-2022. The theory used in this research is legitimacy theory. The population of this research were 61 energy companies registered on the Indonesia Stock Exchange in 2019-2022. The selection of research sample used a purposive sampling technique with specific criteria, resulted 43 samples with 172 total observations. The data used in this research is secondary data obtained from annual reports and/or company sustainability reports. The data analysis technique used is multiple linear regression analysis with the tools of SPSS. The results of this research showed that, 1) public ownership has no effect towards the environmental disclosure, 2) company size has a positive effect towards the environmental disclosure, 3) environmental performance has a positive effect towards the environmental disclosure, and 4) profitability has a positive effect towards environmental disclosure.